PAJAK PENGHASILAN DAN ZAKAT PENGHASILAN - Suryadi Poerbo (Politeknik Negeri Semarang, 2017)
To finance state management, such as paying employees, maintaining people's health,maintaining government buildings, the government needs funds. One source of funds for thegovernment is tax. One of the taxes collected by the government is Income Tax. Every personwho has a certain amount of income, is required to set aside a portion of his income to payincome tax. In Islam, to its adherents, it is subject to the obligation to pay zakat. Zakat is aproperty that must be issued by a Muslim or business entity to be given to those who are entitledto receive it in accordance with Islamic law. One of the things related to zakat, is income. Allforms of income must be paid zakat. To ease the burden of collecting income tax and zakatincome, the government issued a regulation that recognizes income zakat payments can reducetaxable income, which in turn reduces the amount of income tax that must be paid